How do you add (-5-2i)+(7-6i)(52i)+(76i) in trigonometric form?

1 Answer
Jul 15, 2017

(-5-2i) +(7-6i) = 2sqrt17(cos1.33-isin1.33)(52i)+(76i)=217(cos1.33isin1.33)

Explanation:

(-5-2i)+(7-6i) = 2-8i(52i)+(76i)=28i

This can be written in trigonometric form as:

a+bi = r(cosvartheta + i sinvartheta)a+bi=r(cosϑ+isinϑ) where r=sqrt (a^2+b^2)r=a2+b2 and vartheta = arctan(y/x)ϑ=arctan(yx)

sqrt(2^2+(-8)^2) = 2sqrt1722+(8)2=217

arctan(-8/2) = -1.33arctan(82)=1.33

therefore 2-8i = 2sqrt17(cos(-1.33) + isin(-1.33))

Using the properties of the sin and cos functions, this can be rewritten as:

2-8i=2sqrt17(cos1.33-isin1.33)